Reinstatement of Leda rhytida Dall, 1908 and its reallocation into Propeleda (Bivalvia: Nuculanidae) - Güller, Marina (2015)
In 1908, Dall described “Leda” rhytida as occurring off Acapulco, Mexico. The species was never figured, and has no subsequent published records. Despite that, it appears mentioned by several authors in check-lists. The identity of this species appears as controversial in the literature: some authors emended the type locality to either eastern South America or Chile, and the species was regarded either as a possible synonym of Propeleda longicaudata (Thiele, 1912), or considered as a nomen dubium. The aims of this study are to determine the actual provenance of the type material, to provide a proper redescription of the species, and to revise its generic placement and current status. The study of the syntypes and additional material from museum collections reveals that the species actually comes from southern Chile. Based on the elongated shell outline and distinctive hinge morphology, the species is here reallocated into Propeleda. Comparison of this species with P. longicaudata establishes that P. rhytida is a distinct and valid species.